DIGITAL ERA BUSINESS COMMUNICATION: HOW SKINCARE BRAND AMBASSADORS BOOST CUSTOMER ENGAGEMENT - Kania Octa Faradillah; Cecep Saeful Barakah; Nurillah Jamil Achmawati; Iwan Sukoco (Jurnal Manajemen Sains dan Organisasi, 2024)
Objective – The purpose of this study is to determine the effectiveness of Jeon Somi in enhancing customer engagement on social media and how it impacts customer loyalty. Design/Methodology/Approach – This research was conducted using a descriptive qualitative method with a literature review approach. Data were collected through observation of Jeon Somi's activities on social media, online data searches, and literature studies. Findings – The results show that Jeon Somi successfully increased customer engagement through campaigns such as the #SnailDanceChallenge on TikTok, which garnered over 5.3 million views and an engagement rate of 7.3%. Additionally, Jeon Somi's Instagram account generated more than 150 thousand likes and positive comments, further enhancing customer engagement. Conclusion and Implications – This study highlights the importance of using influencers in digital marketing strategies and how public figures like Jeon Somi can boost customer engagement, loyalty, and brand image.